Glycocalyx Engineering with a Recycling Glycopolymer that Increases Cell Survival In Vivo. (13th November 2015) - Woods, Elliot C.; Yee, Nathan A.; Shen, Jeff; Bertozzi, Carolyn R.
Abstract: Synthetic glycopolymers that emulate cell‐surface mucins have been used to elucidate the role of mucin overexpression in cancer. However, because they are internalized within hours, these glycopolymers could not be employed to probe processes that occur on longer time scales. In this work, we tested a panel of glycopolymers bearing a variety of lipids to identify those that persist on cell membranes. Strikingly, we found that cholesterylamine (CholA) anchored glycopolymers are internalized into vesicles that serve as depots for delivery back to the cell surface, allowing for the display of cell‐surface glycopolymers for at least ten days, even while the cells are dividing. As with native mucins, the cell‐surface display of CholA‐anchored glycopolymers influenced the focal adhesion distribution. Furthermore, we show that these mimetics enhance the survival of nonmalignant cells in a zebrafish model of metastasis. CholA‐anchored glycopolymers therefore expand the application of glycocalyx engineering in glycobiology. Abstract : Glykopolymere mit unterschiedlichen Lipid‐Substituenten wurden zur Identifizierung von Derivaten mit hoher Persistenz auf Zellmembranen verwendet. Cholesterylamin‐verankerte Glykopolymere werden internalisiert, aber auch rezykliert und ermöglichen so den kontinuierlichen Display von Zelloberflächen‐Glykopolymeren für zehn Tage. Zudem verbessern diese Mimetika das Überleben nicht maligner Zellen in einem Zebrafisch‐Metastasenmodell.